The Corporate Social Responsibility Islamic Perspective on Furniture Business Players at UD. Winir Putra - Ziadatun Kholishoh Zia; Fetria Eka Yudiana (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
All forms of business are no longer faced with responsibilities that are based not only on the value of the business but also on social and environmental issues. This study aims to explain the implementation of Corporate Social Responsibility at UD Winir Putra from an Islamic Perspective. The research method used is descriptive qualitative through a case study approach by conducting interviews with UD business owners, Winir Putra, employees, and the community around the business in Rembes Hamlet, Gesikharjo Village, Palang District, Tuban Regency. The results of the study show that UD. Winir Putra has implemented forms of social responsibility, including social responsibility towards corporate actors and stakeholders, social responsibility towards the natural environment, and social responsibility towards social welfare in general. As well as from an Islamic perspective, the forms of implementing social responsibility are carried out by UD. Winir Putra has fulfilled the elements of CSR in Islam, namely, the elements of justice, the elements of kindness, the elements of benefits, and the elements of trust. The focus of this research is the implementation of CSR from an Islamic perspective in microenterprises and as a reference for others to develop forms of social responsibility